Penerapan Lingkungan Sebagai Sumber Belajar Terhadap Hasil Belajar IPAS Siswa Kelas III di SDN 51 Sungai Raya - Sari, Sulistiya; Fatmawati, Risdiana Andika; Hertati, Elvani (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to describe the implementation of the environment as a learning resource on the learning outcomes of Science and Social Studies (IPAS) for third grade students at SDN 51 Sungai Raya. The type of research used is descriptive quantitative. The research subjects were 25 third grade students. Data were collected through observation, learning outcome tests, and documentation. The data obtained were analyzed using descriptive quantitative methods by calculating the mean score, percentage, and categories of students’ learning outcomes. The results of the study indicate that the implementation of the environment as a learning resource has a positive effect on students’ IPAS learning outcomes. This is evidenced by the increased student engagement during the learning process and the achievement of learning outcomes categorized as very good. Therefore, utilizing the environment as a learning resource can serve as an effective alternative learning strategy to improve IPAS learning outcomes in elementary schools